Complete Heart Block in Thyrotoxicosis, Is It a Manifestation of Thyroid Storm? A Case Report and Review of the Literature. (11th August 2012) - Al Bannay, Rashed; Husain, Aysha; Khalaf, Saeed
Abstract : Thyrotoxicosis complicated by advance degree atrioventricular block, a rare complication of a common disease. The term apathetic thyrotoxicosis, where palpitations and cardiac involvement are the sole manifestations of disease, is well known. Thyroxin's ability to sensitize the catecholamine receptors causing tachyarrhythmias is well addressed. However, as an aetiology for advanced heart block, thyrotoxicosis is ranked as one of the rarest.